PENGUATAN HUKUM TENTANG PERJANJIAN KREDIT PADA KOPERASI SIMPAN PINJAM BAGI MASYARAKAT DESA PEKIK NYARING - Wafiya; Edi Hermansyah (Adiba Aisha Amira, 2026)
This Community Service Program (Pengabdian kepada Masyarakat/PKM) aimed to provide legal understanding to the community of Pekik Nyaring Village regarding the importance of valid, fair, and transparent credit agreements in savings and loan cooperatives. Through counseling activities, training sessions, and legal assistance, cooperative members and management were expected to understand their respective rights and obligations in credit agreements. The activities were conducted using interactive counseling methods, training on the drafting of credit agreements, and group discussions. The results showed an improvement in the participants’ legal understanding, as evidenced by their ability to explain the essential elements of a valid agreement and their increased awareness of the importance of clear and well-documented written agreements.